2013
DOI: 10.5172/jfs.2013.19.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation and the desires and intentions to become parents

Abstract: This is the first study in Italy to evaluate parenting desires and intentions, the value of parenthood and individual perception of competence as a parent in an Italian sample of lesbian women (N = 201), gay men (N = 199) and heterosexual participants (female = 314 and male = 216) 18-35 years of age. Childless lesbian and gay individuals were less likely than their heterosexual peers to report parenting desires and intentions. Data suggested that lesbians and gay male participants reported a lower level of enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
95
7
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(140 citation statements)
references
References 1 publication
22
95
7
3
Order By: Relevance
“…Finally, with regard to adoption by same-sex couples, only 19% of Italians are favourable (Eurispes, 2009). Regarding the attitude of gay men and lesbians towards same-sex families and their intention to become parents, studies conducted in the Italian context showed that they have a positive attitude toward same-sex family legalization, but they have lower desire and intentions to become parents as compared to heterosexuals; moreover, these variables are negatively related to internalised sexual stigma (Baiocco et al, 2014;Baiocco & Laghi, 2013). These results indicate that Italian gay men and lesbians have, in some way, complied with the impossibility to have a recognized family in Italy.…”
Section: Context Of the Studymentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, with regard to adoption by same-sex couples, only 19% of Italians are favourable (Eurispes, 2009). Regarding the attitude of gay men and lesbians towards same-sex families and their intention to become parents, studies conducted in the Italian context showed that they have a positive attitude toward same-sex family legalization, but they have lower desire and intentions to become parents as compared to heterosexuals; moreover, these variables are negatively related to internalised sexual stigma (Baiocco et al, 2014;Baiocco & Laghi, 2013). These results indicate that Italian gay men and lesbians have, in some way, complied with the impossibility to have a recognized family in Italy.…”
Section: Context Of the Studymentioning
confidence: 98%
“…For example, studies conducted in Italy, with gay males and lesbian participants, Religious Orientation,Secularism,and Gay Rights 83 showed that 56.3% of lesbians and 40.3% of gay men desire to marry (Baiocco et al, 2014); and 51.8% of gay men and 60.7% of lesbians desire to become parents (Baiocco & Laghi, 2013). However, the discussion on the regulation of sexual minorities' rights, such as same-sex marriage and adoption by same-sex couples, continues to generate disagreement.…”
Section: Introductionmentioning
confidence: 97%
“…Despite the legal vacuum and the homophobic stigma (Baiocco et al, 2015;Lingiardi et al, 2016), an increasing number of gay men and lesbian women are becoming parents (Baiocco and Laghi, 2013;Baiocco et al, 2014). When lesbian women decide to have children within their current relationship, they have to turn to third-party reproduction offering a spectrum of possibilities regarding both donor arrangement (from open-identity to anonymous) and degrees of familiarity with the donor (from family members to strangers living in other countries).…”
Section: Introductionmentioning
confidence: 96%
“…Salienta-se que a nova lei da adoção, nº 12.010/2009, e como parte da população se mostrando adepta, é sabido que há entre os casais homossexuais um receio em adotar, posto que ainda existem barreiras psicossociais e institucionais inerentes ao processo de adoção na famí-lia homoparental na vida em sociedade (Baiocco & Laghi, 2013).…”
Section: Discussionunclassified